2013
DOI: 10.1016/j.ijid.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of OXA-48- and NDM-1-positive Klebsiella pneumoniae in Riyadh, Saudi Arabia

Abstract: Multidrug-resistant K. pneumoniae isolates harboring blaOXA-48, blaNDM, and colistin resistance are emerging in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
108
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 37 publications
17
108
1
Order By: Relevance
“…bla CTX-M group1 genes were detected in eight of the nine isolates. In another study, of the 60 K. pneumoniae with reduced susceptibility to carbapenem collected in 2011 (Shibl et al, 2013), 47 (78 %) carried the OXA-48 gene, while NDM-1 and VIM were found in 20 and 1.6 % of the isolates, respectively. None of the isolates harboured a combination of the three resistance genes or KPC.…”
Section: Carbapenemase Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…bla CTX-M group1 genes were detected in eight of the nine isolates. In another study, of the 60 K. pneumoniae with reduced susceptibility to carbapenem collected in 2011 (Shibl et al, 2013), 47 (78 %) carried the OXA-48 gene, while NDM-1 and VIM were found in 20 and 1.6 % of the isolates, respectively. None of the isolates harboured a combination of the three resistance genes or KPC.…”
Section: Carbapenemase Productionmentioning
confidence: 95%
“…All these studies were from Riyadh and report the emergence of OXA-48 and NDM-1, especially among K. pneumoniae. Al- Agamy et al (2013) characterized nine resistant K. pneumoniae isolated from Riyadh hospitals in 2011. They detected OXA-48 and NDM carbapenemases in 77.7 and 22.2 % of the isolates, respectively.…”
Section: Carbapenemase Productionmentioning
confidence: 99%
“…Recent study from Riyadh confirmed the emergence of OXA-48 and NDM-1 among K. pneumoniae in which 12 out of 60 K. pneumoniae strains were NDM-1 producers and 47/60 strains were positive for OXA-48. No strain was positive for KPC [16]. Compared to above mentioned studies, current study reports a high percentage of K. pneumoniae (48.4%) isolates to be carbapenemase producers determined by Modified Hodge Test (MHT).…”
Section: Discussionmentioning
confidence: 58%
“…Recent studies conducted in Middle East countries also suggests that this region might be an additional reservoir of NDM producers as it has been reported from Oman [13], Lebanon [14], Saudi Arabia [15,16], and Qatar [17].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation